Analisis Kualitas Produk Solid Flooring untuk Meminimasi Cacat dengan Metode Six Sigma dan FMEA - Muhammad Ricky Suryawan; Rr. Rochmoeljati (Journal of Creative Student Research, 2023)
PT. Kali Jaya Putra is a manufacturing company that focuses on the production of wood floors. One of the products produced is solid flooring. In a series of production processes, product defects are still found up to 7.5% of total production, defects that often occur such as cracks, pinholes, roughness, and also twists which certainly affect product quality. The research conducted aims to determine the percentage of defective products, the causes of defects and the resulting impacts or effects, and to provide recommendations for improvements to minimize the percentage of defects in solid flooring products at PT Kali Jaya Putra. The method used is Six Sigma and Failure Mode and Effect Analysis (FMEA). The results of this study are that the most dominating defects are crack (53.75%), followed by pinhole defects (36.77%), twist (8.62%), and roughness (0.85%). The causes of defects in products are caused by several factors such as humans, machines, methods, materials, and the environment. Based on FMEA, it is known that the cause of the defect with the highest RPN is 384, namely operator negligence in material sorting. As for recommendations for improvement that can be given, namely conducting training on the grading of raw materials in the hope of minimizing operator errors in sorting raw materials.